Pharmacoeconomics: Need for the day - Iram, Mahvash; Rani. R.Hiremath, Shobha (Indian Journal of Pharmacy Practice)
Health economics shed's light on the concept of making decisions about resource allocations at the time of scarcity of resources and increased demand, by evaluating the rationale of choices in terms of their cost and benefit. Pharmacoeconomics is one of the strongest pillars of health economics to make the allocation decisions with respect to the medicines and there by ensure that society allocates minimal health care resources wisely, fairly, and efficiently. Two major components of any pharmacoeconomic evaluation are cost and consequences and using pharmacoeconomic principles, methods and theories into practice, for quantifying the value of pharmacy products and pharmaceutical care services utilized in real world environment is one of the major applications of pharmacoeconomics. The key reason for studying pharmacoeconomics is to be able to estimate, understand and interpret the complete impact of a drug therapy. Such an impact would be shown on individual's health, safety, their use of health care services, cost of health care, quality of life, functional status and on society as a whole. The price of drug therapy will be then justified based on its impact on broad range of outcomes.
Keywords: Pharmacoeconomics; cost; consequences; health care; benefit